Apoptosis induced by mercuric chloride is associated with upregulation of PERK-ATF4-CHOP pathway in chicken embryonic kidney cells - Yan Ma; Yizhen Shi; Xiaoting Zou; Qiujue Wu; Jianping Wang (Poultry Science, 2020)
Mercuric chloride (HgCl2) is a serious environmental toxicant. So far, the toxicity mechanism of HgCl2 in chicken embryonic kidney (CEK) cells is not still fully understood. In this study, the possible molecular mechanisms of HgCl2 on apoptosis of CEK cells were investigated. Results showed that the cell morphology changed, and cell viability was significantly decreased (P < 0.05) after HgCl2 exposure. Besides, apoptosis rate was significantly increased after HgCl2 exposure (P < 0.05). The gene and protein expressions of B-cell lymphoma-2 associate X/B-cell lymphoma-2 (P < 0.05), caspase-3 (P < 0.05), and caspase-9 (P < 0.05) were significantly enhanced by HgCl2 in CEK cells. We also found that intracellular reactive oxygen species level was significantly enhanced (P < 0.05), and the flux of calcium ion to mitochondria occurred after HgCl2 exposure. In terms of molecular mechanisms, the mRNA and protein expressions associated with endoplasmic reticulum (ER) stress were significantly increased after HgCl2 exposure (P < 0.05), including glucose regulated protein 78, protein kinase RNA-like endoplasmic reticulum kinase (PERK), activating transcription factor 4 (ATF4), and C/EBP homologous protein (CHOP). However, pretreated with 1-μmol/L 4-phenylbutyrate (ER stress inhibitor) alleviated the apoptosis and downregulated PERK-ATF4-CHOP pathway in CEK cells. Taken together, upregulation of PERK-ATF4-CHOP pathway of ER stress induced by HgCl2 is associated with apoptosis in CEK cells.